2019
DOI: 10.1364/oe.27.008081
|View full text |Cite
|
Sign up to set email alerts
|

Mode coupling by scattering in chiral nematic liquid crystal ring lasing

Abstract: Lasing in dye-doped chiral nematic liquid crystal can be realized with low pump energy and relatively high efficiency, thanks to the high reflectivity of the periodic structure. When the helical axis is oriented perpendicular to the substrates, the main lasing peak is normal to the substrates. In some cases, ring lasing of a particular wavelength is observed into an emission cone with axial symmetry. In this paper we explain how scattering of light in the liquid crystal layer leads to optical coupling between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…An investigation of the stop-band structure for an oblique incidence using fluorescence in the framework of the linear optics was reported in [28]. The EM and CEM coupling was also recently investigated in [29], where, in particular, was found that a focusing of the pumping wave promotes the coupling realization (which is in a full agreement with the above discussion).…”
Section: Possible Coupling Between Localized Modessupporting
confidence: 56%
“…An investigation of the stop-band structure for an oblique incidence using fluorescence in the framework of the linear optics was reported in [28]. The EM and CEM coupling was also recently investigated in [29], where, in particular, was found that a focusing of the pumping wave promotes the coupling realization (which is in a full agreement with the above discussion).…”
Section: Possible Coupling Between Localized Modessupporting
confidence: 56%